How Cues of Being Watched Promote Risk Seeking in Fund Investment in Older Adults - Li, Meijia; Peng, Huamao (Frontiers in Psychology, 2022)
Social cues, such as being watched, can subtly alter fund investment choices. This study aimed to investigate how cues of being watched influence decision making, attention allocation, and risk tendencies. Using decision scenarios adopted from the “Asian disease problem”, we examined participants’ risk tendency in a financial scenario when they were watched. A total of 63 older and 66 younger adults participated. Eye tracking was used to reveal the decision maker’s attention allocation (fixations and dwell time per word). The results found that both younger and older adults tend to seek risk in the loss frame than in the gain frame (i.e., framing effect). Watching eyes tended to escalate reckless gambling behaviors among older adults, which led them to maintain their share in the depressed fund market, regardless of whether the options were gain- or loss-framed. The eye-tracking results revealed that older adults gave less attention to the sure option in the eye condition (i.e., fewer fixations and shorter dwell time). However, their attention was maintained on the gamble options. In comparison, images of “watching eyes” did not influence the risk seeking of younger adults but decreased their framing effect. Being watched can affect financial risk preference in decision making. The exploration of the contextual sensitivity of being watched provides us with insight into developing decision aids to promote rational financial decision making, such as human-robot interactions. Future research concerning age differences still requires further replication.